Performance comparison of transformer-based models for multi-reasoning in machine reading comprehension - Sayma, Sadika; Tonima, Fariha Hasan; Biswas, Sourav; Ferdos, Jannatul; Haque, Tasnuva (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.